PR Model of Garuda Indonesia: A Construction of Wonderland Through Instagram - Daniel Susilo; Charles Julian Santos Navarro (Indonesian Journal of Business Analytics, 2023)
Social Media is an integral part of branding, not only through ads or influencers but even through one-way communication and one-way truth can defy one of the dark records from big Indonesian SOEs like Garuda Indonesia. Through Garuda Indonesia Instagram post, we can identify the concept constructed by Garuda Indonesia which is not only for their own company but a Mega-PR concept. From one brand to another that is linked to government institutions, Garuda Indonesia’s Instagram post is showing a way to survive heavy financial and PR damage through a simple public information model and it doesn’t require complex techniques to do it and only through a digital device that they can escape the downfall from social media controversy.